2012
DOI: 10.1155/2012/249687
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable Pins for Treatment of Osteochondral Fractures of the Knee after Acute Patella Dislocation in Children and Young Adolescents

Abstract: A retrospective study was performed on the use of bioabsorbable pins in the fixation of osteochondral fractures (OCFs) after traumatic patellar dislocation in children. Eighteen children (13 females, 5 males) aged 11 to 15 years (mean age 13.1 years) with osteochondral fracture (OCF) of the knee joint were treated at the authors' institution. Followup ranged from 22 months to 5 years. Diagnosis was verified by X-ray and magnetic resonance imaging (MRI) of the knee and patella. In seven patients the osteochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 15 publications
(19 reference statements)
0
21
0
Order By: Relevance
“…There are various kinds of effective methods aiming at osteochondral lesions or full-thickness chondral lesions of the articular cartilage, including fixation techniques, bone-marrow stimulation techniques, osteochondral grafting (autograft and allograft) and autologous chondrocyte implantation (ACI), whereas there is a lack of effective methods for partial-thickness chondral defects [10,20,[40][41][42][43][44][45][46][47][48][49][50][51]. Hence, the identification of osteochondral lesions may be of more significant value in clinical treatment selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various kinds of effective methods aiming at osteochondral lesions or full-thickness chondral lesions of the articular cartilage, including fixation techniques, bone-marrow stimulation techniques, osteochondral grafting (autograft and allograft) and autologous chondrocyte implantation (ACI), whereas there is a lack of effective methods for partial-thickness chondral defects [10,20,[40][41][42][43][44][45][46][47][48][49][50][51]. Hence, the identification of osteochondral lesions may be of more significant value in clinical treatment selection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evaluation of MPFL tears after LPD in children and adolescents has been described in a few papers, there still remains some conflicts about the main rupture location of the MPFL [3][4][5][6][7][8][9]. Although there were some studies about articular cartilage lesions of the inferomedial patella and the lateral femoral condyle [4,5,[10][11][12][13][14][15][16][17][18][19][20][21], there were no studies concentrating on the correlations between the injury patterns of the MPFL and articular cartilage lesions of the lateral femoral condyle in children and adolescents. Therefore, we undertook this prospective magnetic resonance imaging (MRI) study to investigate the injury characteristics of the MPFL, as well as the correlations between the injury patterns of the MPFL and articular cartilage lesions of the lateral femoral condyle after acute LPD in children and adolescents.…”
mentioning
confidence: 99%
“…These results revealed that currents could be transformed from mechanical strain, while movement in piezoelectric PLLA scaffolds can help promote bone growth. Due to its biodegradability, non-toxicity, and advantageous mechanical properties, PLLA has substantial promise for use in clinical applications as biodegradable screws, fixation pins, and suture anchors in an effort to avoid a second surgery for removal of the implants [68][69][70] (Figure 9). These types of absorbable screws and pins have been gaining in their clinical use, particularly in cases where high mechanical stiffness and/or strength is not required [71].…”
Section: Plla (Poly-l-lactic Acid)mentioning
confidence: 99%
“…Available articles are primarily based on case reports and low-number case series [2,[5][6][7][8][9][10][11]. Only a few articles are based on large case series with clinical and MRI follow-up [3,12]. Depending on the fragment size and fractured subchondral bone thickness, different surgical procedures are applied to treat OCF: fixation with headless metal screws or bioabsorbable pins or suture [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few articles are based on large case series with clinical and MRI follow-up [3,12]. Depending on the fragment size and fractured subchondral bone thickness, different surgical procedures are applied to treat OCF: fixation with headless metal screws or bioabsorbable pins or suture [11][12][13][14]. If the subchondral bone is too small, it is necessary to remove a fractured fragment, apply the microfracture technique, or make use of some other means of chondral plasty [4].…”
Section: Introductionmentioning
confidence: 99%